Staff-reported barriers and facilitators to the implementation of healthcare interventions within regional and rural areas: a rapid review - Anna Chapman; Alison Buccheri; Devdini Mohotti; Anna Wong Shee; Catherine E. Huggins; Laura Alston; Alison M. Hutchinson; Sze Lin Yoong; Hannah Beks; Kevin Mc Namara; Anna Peeters; Anna Ugalde (BMC Health Services Research)
Abstract Background Individuals in rural areas consistently demonstrate higher mortality and morbidity rates, and poorer access to healthcare, compared to their metropolitan counterparts. Optimizing the implementation of evidence-based interventions can reduce these inequities. Existing literature outlines numerous barriers and facilitators to the implementation of healthcare interventions, but these are generally not specific to rural areas. This rapid review aims to synthesize barriers and facilitators to the implementation of healthcare interventions in regional and rural healthcare services as reported by healthcare staff, including clinicians, managers, and administrators. Methods A systematic search for peer-reviewed publications was conducted using CINAHL, PsycINFO, Medline, and Embase databases (1/1/2000–29/08/2023). Eligible publications were primary research articles published in English, assessing staff-reported barriers and facilitators to implementing healthcare interventions within regional and rural areas of high-income countries. Qualitative, quantitative, and mixed-methods designs were included. Eligible healthcare settings encompassed acute, sub-acute, primary care, community health, and aged care. Barrier and facilitator data were coded and grouped into sub-themes and broader themes, with results presented narratively. Results Thirty-nine publications met the inclusion criteria. Most studies were conducted in Australia or the USA (both n = 18, 46%), within primary care (n = 13, 33%) or hospital settings (n = 12, 31%) in rural (n = 22, 56%) or regional (n = 9, 23%) locations. Implementation barriers and facilitators were grouped into four overarching themes: intervention-level (intervention feasibility and fit; complexity; privacy and confidentiality); staff-level (staff attitudes and beliefs; knowledge, skills, and confidence; staff roles and professional identity), patient-level (patient characteristics; attitudes), and system-level (leadership support; environmental resources and context; geographic vastness; networks and communication). Conclusions These findings provide essential guidance for policymakers, healthcare leaders, and researchers in planning and designing future implementation efforts in regional and rural healthcare settings. By considering factors across intervention, staff, patient, and system levels, stakeholders can address challenges and leverage local strengths to enhance implementation success and reduce health disparities. Trial registration PROSPERO registration number: CRD42023470736. Registered 19/10/2023.